Prevention of Vitamin K Deficiency Bleeding in Newborn Infants: A Position Paper by the ESPGHAN Committee on Nutrition. Issue 1 (July 2016) - Mihatsch, Walter A.; Braegger, Christian; Bronsky, Jiri; Campoy, Cristina; Domellöf, Magnus; Fewtrell, Mary; Mis, Nataša F.; Hojsak, Iva; Hulst, Jessie; Indrio, Flavia; Lapillonne, Alexandre; M⊘lgaard, Christian; et al.
Abstract : ABSTRACT: Vitamin K deficiency bleeding (VKDB) due to physiologically low vitamin K plasma concentrations is a serious risk for newborn and young infants and can be largely prevented by adequate vitamin K supplementation. The aim of this position paper is to define the condition, describe the prevalence, discuss current prophylaxis practices and outcomes, and to provide recommendations for the prevention of VKDB in healthy term newborns and infants. All newborn infants should receive vitamin K prophylaxis and the date, dose, and mode of administration should be documented. Parental refusal of vitamin K prophylaxis after adequate information is provided should be recorded especially because of the risk of late VKDB. Healthy newborn infants should either receive 1 mg of vitamin K1 by intramuscular injection at birth; or 3 × 2 mg vitamin K1 orally at birth, at 4 to 6 days and at 4 to 6 weeks; or 2 mg vitamin K1 orally at birth, and a weekly dose of 1 mg orally for 3 months. Intramuscular application is the preferred route for efficiency and reliability of administration. The success of an oral policy depends on compliance with the protocol and this may vary between populations and healthcare settings. If the infant vomits or regurgitates the formulation within 1 hour of administration, repeating the oral dose may be appropriate. The oral route is not appropriate for preterm infants and for newborns who have cholestasis or impaired intestinal absorption or are too unwell to take oral vitamin K1, or those whose mothers have taken medications that interfere with vitamin K metabolism. Parents who receive prenatal education about the importance of vitamin K prophylaxis may be more likely to comply with local procedures.